EFEKTIVITAS PEMBERIAN NANOPARTIKEL EKSTRAK DAUN JUWET (Syzygium cumini) SEBAGAI ADJUVANT TERAPI TERHADAP GAMBARANHISTOPATOLOGI PULMO MENCIT (Mus musculus) YANG DIINFEKSI Plasmodium bhergei - Ayu, Zerlinda Dyah; Maslachah, Lilik; Supranianondo, Koesnoto; Suprihati, Endang; Plumeriastuti, Hani; Sugihartuti, Rahmi (Universitas Airlangga, 2020)
The purpose of this study was to learn how to use juwet nanoparticle leaf extract (Syzygium cumini) as an adjunct therapy in pulmonary histopathological mice (Mus musculus) supported by Plasmodium berghei. This study used 30 rats divided into six groups consisting of K0 (disagree without agreement), P1 (fight without agreement), P2 (fight and dispute with chloroquine), P3 (fight and talk with juwet leaf extract), P4 (useful and useful with juwet leaf extract)) and P5 (extracts and combinations given with chloropine and juwet leaf extract nanoparticles) protected by 1x105 in 0.2 ml of Plasmodium berghei. Data were analyzed by Kruskal Wallis using SPSS and continued with the Mann-Whitney test. The results of this study showed that there were significant differences (p <0.05) between P2 and P5, but did not show a significant difference (p> 0.05) with P1, P3 and P4. Based on this study, can be witnessed by juwet nanoparticles (Syzygium Cumini) additional therapeutic leaf extract which is expected to reduce pulmonary damage (hemmoragi, alveolar congestion, edema, hemosiderin) mice (Mus musculus) infected with Plasmodium berghei.